Isolation of a spontaneous cerulenin-resistant sake yeast with both high ethyl caproate-producing ability and normal checkpoint integrity. Issue 7 (3rd July 2015) - Tamura, Hiroyasu; Okada, Hiroki; Kume, Kazunori; Koyano, Takayuki; Goshima, Tetsuya; Nakamura, Ryo; Akao, Takeshi; Shimoi, Hitoshi; Mizunuma, Masaki; Ohya, Yoshikazu; Hirata, Dai
Abstract: In the brewing of high-quality sake such as Daiginjo - shu, the cerulenin-resistant sake yeast strains with high producing ability to the flavor component ethyl caproate have been used widely. Genetic stability of sake yeast would be important for the maintenance of both fermentation properties of yeast and quality of sake. In eukaryotes, checkpoint mechanisms ensure genetic stability. However, the integrity of these mechanisms in sake yeast has not been examined yet. Here, we investigated the checkpoint integrity of sake yeasts, and the results suggested that a currently used cerulenin-resistant sake yeast had a defect in spindle assembly checkpoint (SAC). We also isolated a spontaneous cerulenin-resistant sake yeast FAS2 - G1250S mutant, G9CR, which showed both high ethyl caproate-producing ability and integrity/intactness of the checkpoint mechanisms. Further, morphological phenotypic robustness analysis by use of CalMorph supported the genetic stability of G9CR. Finally, we confirmed the high quality of sake from G9CR in an industrial sake brewing setting. Graphical abstract: : Cerulenin (lower structure)-resistant sake yeast G9CR (green/cell wall, red/actin, blue/nucleus) with both high productivity of ethyl caproate (upper structure) and normal checkpoint integrity.